Optimal Designs Of Univariate And Multivariate Synthetic Control Charts Based On Median Run Length - Wong, Voon Hee (2012)
Univariate and multivariate control charts are usually optimally designed using average run length (ARL) as a sole measure of the charts’ performances. It is well known that the shape of the run length distribution for the univariate and multivariate charts changes from highly skewed when the process is in-control to approximately symmetric for large process shifts. Therefore, the median run length (MRL) is a more meaningful interpretation of the in-control and out-of-control performances of the charts and provides additional information not given by the average run length (ARL).